Epigenetic silencing of SALL2 confers tamoxifen resistance in breast cancer - Liping Ye; Chuyong Lin; Xi Wang; Qiji Li; Yue Li; Meng Wang; Zekun Zhao; Xianqiu Wu; Dongni Shi; Yunyun Xiao; Liangliang Ren; Yunting Jian; et al. (EMBO Molecular Medicine)
Abstract Resistance to tamoxifen is a clinically major challenge in breast cancer treatment. Although downregulation of estrogen receptor‐alpha (ERα) is the dominant mechanism of tamoxifen resistance, the reason for ERα decrease during tamoxifen therapy remains elusive. Herein, we reported that Spalt‐like transcription factor 2 (SALL2) expression was significantly reduced during tamoxifen therapy through transcription profiling analysis of 9 paired primary pre‐tamoxifen‐treated and relapsed tamoxifen‐resistant breast cancer tissues. SALL2 transcriptionally upregulated ESR1 and PTEN through directly binding to the DNA promoters. By contrast, silencing SALL2 induced downregulation of ERα and PTEN and activated the Akt/mTOR signaling, resulting in estrogen‐independent growth and tamoxifen resistance in ERα‐positive breast cancer. Furthermore, hypermethylation of SALL2 promoter was found in tamoxifen‐resistant breast cancer. Importantly, in vivo experiments showed that DNA methyltransferase inhibitor‐mediated SALL2 restoration resensitized tamoxifen‐resistant breast cancer to tamoxifen therapy. These findings shed light on the mechanism of SALL2 in regulation of ER and represent a potential clinical signature that can be used to categorize breast cancer patients who may benefit from co‐therapy with tamoxifen and DNMT inhibitor.